The role of polymorphisms rs12218 of the SAA1 gene, rs1205 of the CRP gene, and rs7574865 of the STAT4 gene in the formation of predisposition to panniculitis in the Russian cohort of patients (pilot study) - M. Yu. Krylov; O. N. Egorova; N. V. Konovalova; D. A. Varlamov (Современная ревматология, 2022)
Objective: to study the role of SAA1, CRP and STAT4 gene polymorphisms in the development of panniculitis (PN) and their relationship with clinical and laboratory parameters in the Russian cohort of patients.Patients and methods. The study included 74 patients (67 women and 7 men aged 15 to 76 years) with diagnosis of PN. In addition to the general clinical examination, immunological and histological studies, computed tomography of the chest, and tuberculin tests were performed. For genetic study, two groups of patients were formed: with septal PN (SPN, n=26), represented by erythema nodosum (EN) and with lobular PN (LPN, n=48), including predominantly with idiopathic LPN (iLPN, n= 18) and other rare variants (n=30). As a control, the results of DNA genotyping of 142 healthy non-related individuals were used. Genotyping of polymorphisms rs12218 of the SAA1 gene, rs1205 of the CRP gene, and rs7574865 of the STAT4 gene was performed by the allele-specific real-time polymerase chain reaction.Results and discussion. Significant differences were found between the groups in terms of age and duration of the disease. Patients with SPN were younger than those with LPN (p=0.013), had a shorter duration of the disease (p=0.001), and a lower ESR (p=0.001). Carriers of the TT genotype of the SAA1 gene polymorphism were twice as likely to develop LPN as compared to controls (odds ratio, OR 2.25; 95% confidence interval, CI 1.04–4.87; p=0.038), and this genotype was regarded as a risk factor. For patients with SPN, a significant risk factor was identified in the form of carriage of the mutant TT genotype of the CRP gene polymorphism. This genotype increased the predisposition to the development of EN by 4 times compared with the control (OR 4.39; 95% CI 1.26–14.11; p=0.009). There was a 6-fold increase in the risk of developing EN in carriers of the TT mutant genotype and the T allele of the STAT4 gene polymorphism compared with the control (OR 5.89; 95% CI 1.14–31.75; p=0.016 and OR 2.07; 95 % CI 0.99–4.19, p=0.030, respectively). Comparison of the frequencies of the T allele of the SAA1 gene polymorphism in the groups with EN and with iLPN revealed a higher frequency of the SAA1TT genotype and the SAA1T allele in iLPN than in EN (66.7 and 26.9%, p=0.066; 88.5 and 55.8 %, p=0.016, respectively).Conclusion. The present study confirms the involvement of genetic factors, in addition to generally recognized environmental factors, in the pathogenesis of inflammatory diseases of adipose tissue. Polymorphisms of the SAA1, CRP, and STAT4 genes play a role in the formation of a genetic predisposition to the main clinical phenotypes of PN.